Effect of intestinal microbiota transplantation on chronic hepatitis B virus infection associated liver disease - Deng, Lisi; Guo, Xiaozhen; Chen, Jiehua; Li, Baoyi; Liu, Na; Xia, Jinyu; Ou, Mengdang; Hong, Zhongsi (Frontiers in Microbiology, 2024)
Background Research on the effects of intestinal microbiota transplantation (IMT) on chronic HBV infection (CHB) progression associated liver disease (HBV-CLD) and alterations in the microbiota post-IMT are quite limited for the moment .Methods By integrating microbiome with metabolome analyses, we aimed to the function of IMT and the alterations of gut microbiota in patients with HBV-CLD. First, this study included 20 patients with HBV-CLD and ten healthy controls. Then, 16 patients with CHB were given IMT with donor feces (heterologous) via oral capsule. Fecal samples from CHB patients were obtained before and after IMT, as well as healthy controls, for 16S rDNA sequencing and untargeted metabolomics analysis.The proalbuminemia were significantly increased after IMT, and the HBsAg and TBA showed a significant decrease after IMT in the HBV-CLD patients. There was statistical difference in the Chaol indexes between between CHB patients and healthy controls, suggesting a lower abundance of the gut microbiota in HBV-CLD patients.In addition, there was statistical difference in the Shannon and Simpson indexes between prior to IMT and post-IMT, indicating that the impaired abundance of the gut microbiota had been improved after IMT. The host-microbiota-metabolite interplay, amino acid metabolism, nicotinate and nicotinamide metabolism, starch and sucrose metabolism, steroid biosynthesis, and vitamins metabolism, were significantly lower in HBV-CLD patients than healthy controls.Conclusions IMT may improve the therapeutic effects on patients HBV-CLD. Furthermore, IMT appears to improve amino acid metabolism by impaired abundance of the gut microbiota and therefore improve liver prealbumin synthesis.